Perspectives on menopause and women with HIV - Andany N; Kennedy VL; Aden M; Loutfy M (Dove Medical Press, 2016)
Nisha Andany,1 V Logan Kennedy,2 Muna Aden,2 Mona Loutfy1,2 1Department of Medicine, University of Toronto, Toronto, ON, Canada; 2Women’s College Research Institute, Women’s College Hospital, Toronto, ON, Canada Abstract: Since the implementation of effective combination antiretroviral therapy, HIV infection has been transformed from a life-threatening condition into a chronic disease. As people with HIV are living longer, aging and its associated manifestations have become key priorities as part of HIV care. For women with HIV, menopause is an important part of aging to consider. Women currently represent more than one half of HIV-positive individuals worldwide. Given the vast proportion of women living with HIV who are, and will be, transitioning through age-related life events, the interaction between HIV infection and menopause must be addressed by clinicians and researchers. Menopause is a major clinical event that is universally experienced by women, but affects each individual woman uniquely. This transitional time in women’s lives has various clinical implications including physical and psychological symptoms, and accelerated development and progression of other age-related comorbidities, particularly cardiovascular disease, neurocognitive dysfunction, and bone mineral disease; all of which are potentially heightened by HIV or its treatment. Furthermore, within the context of HIV, there are the additional considerations of HIV acquisition and transmission risk, progression of infection, changes in antiretroviral pharmacokinetics, response, and toxicities. These menopausal manifestations and complications must be managed concurrently with HIV, while keeping in mind the potential influence of menopause on the prognosis of HIV infection itself. This results in additional complexity for clinicians caring for women living with HIV, and highlights the shifting paradigm in HIV care that must accompany this aging and evolving population. Keywords: HIV, women, aging, menopause